79 Does a reduced forced vital capacity compare with abnormal sleep study results?. (30th November 2020) - Griffiths, Ben; Kiran, Sreeja; Martins, Joanne; Brotherston, Stephanie; Davies, Matthew; Laverty, Aidan
Abstract : Introduction: Respiratory deterioration impacts morbidity and mortality in patients with Neuromuscular disorders (NMD). Respiratory involvement will vary by disorder; patients with Duchenne muscular dystrophy (DMD) and Spinal muscular atrophy (SMA) often displaying deterioration with disease progression. Such patients may present with sleep-related breathing disorders (SRBD) which can progress to hypoventilation. Spirometry, including forced vital capacity (FVC) measurements, monitor respiratory muscle strength and sleep studies identify SRBD to determine when non-invasive ventilation is required. Assessing when to refer for a sleep study is therefore clinically important. Previous research suggests the use of FVC <60% of predicted normal (FVCLT60%) may indicate an abnormal sleep study. Aim: To assess if patients with FVCLT60% had an abnormal baseline sleep study. Method: A retrospective study of patients who attended for spirometry between April 2018 - April 2020 with FVCLT60% and a baseline cardiorespiratory sleep study within 3 months of spirometry. Patients were excluded if using night time respiratory support. Apnoea-Hypopnoea Index (AHI) was used to classify SRBD. Fifty-four patients were identified and results reported as mean (±SD). Results: Demographics: Age 14.05 (±2.8) years, 40 male (74%), 30 DMD (56%). Twenty-Two (40.7%) had moderate or severe SRBD (AHI≥5 events/hour), with a mean FVC%predicted of 37.6% (±12.0%). Those with mild or no SRBD (AHI<5 events/hour) showed mean FVC of 44.5% (±9.7%). Conclusion: Our study showed 59% of patients who had FVCLT60% had mild or no SRBD. In our patient group, the use of FVCLT60% may not be appropriate for sleep study referral. A lower FVC threshold may be more appropriate in identifying patients who require treatment for SRBD, but further research is required.